Purulent bacterial pericarditis from Staphylococcus aureus. Issue 7 (28th May 2019) - Kaye, Adam; Peters, Gregory A.; Joseph, Joshua W.; Wong, Matthew L.
Abstract: Purulent pericarditis is a rare condition in the modern antibiotic era. The diagnosis should be suspected in patients with pericardial effusions and radiographic and laboratory investigations consistent with infection. Pericardial fluid culture is the gold standard. Early source control, in addition to antibiotics, is a cornerstone of treatment. Abstract : Purulent pericarditis is a rare condition in the modern antibiotic era. The diagnosis should be suspected in patients with pericardial effusions and radiographic and laboratory investigations consistent with infection. Pericardial fluid culture is the gold standard. Early source control, in addition to antibiotics, is a cornerstone of treatment.